2020
DOI: 10.1021/acsomega.9b03260
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Reclamation of Silver Present in Photographic Waste Using Magnetically Separable TiO2@CuFe2O4 Nanocomposites and Thereof Its Use in Antibacterial Activity

Abstract: In the present investigation, the silver present in photographic waste is reclaimed catalytically using magnetically separable TiO 2 @CuFe 2 O 4 nanocomposites (NCs), and further, the recovered silver nanoparticles [Ag(0) NPs] are tested against the representative bacteria for the antibacterial activity. Initially, a series of the different composites between TiO 2 nanoparticles and CuFe 2 O 4 nanoparticles are synthesized by a sol−gel "ex situ" method to enhance the catalytic activity of bare nanomaterials to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Several studies have reported the photocatalytic activity of copper ferrite and its nanocomposites in water and wastewater treatment [109,111,112].…”
Section: Copper Ferrite and Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the photocatalytic activity of copper ferrite and its nanocomposites in water and wastewater treatment [109,111,112].…”
Section: Copper Ferrite and Nanocompositesmentioning
confidence: 99%
“…More studies on the activity of copper ferrite nanocomposites for the degradation of organic pollutants are listed in Table 2. Several studies have reported the photocatalytic activity of copper ferrite and its nanocomposites in water and wastewater treatment [109,111,112].…”
Section: Copper Ferrite and Nanocompositesmentioning
confidence: 99%
“…Last few decades, several approaches and strategies have been developed to improve the optoelctronic properties of TiO 2 as photocatalyst, which includes doping with metal or non‐metals, formation of composite with other materials, photosensitization and so on [18–21] . On more general grounds, the main purpose of all the studies are to modify TiO 2 to capable it to work in visible light by keeping original network intact [22] .…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] Last few decades, several approaches and strategies have been developed to improve the optoelctronic properties of TiO 2 as photocatalyst, which includes doping with metal or non-metals, formation of composite with other materials, photosensitization and so on. [18][19][20][21] On more general grounds, the main purpose of all the studies are to modify TiO 2 to capable it to work in visible light by keeping original network intact. [22] Modified TiO 2 with doping is one of the effective way to tune the material properties, without disturbing original structure of TiO 2 with a degree of substitution that goes beyond the doping level appears as a challenging and promising way to tailor its properties, which include metal doping, [23,24] non metal doping [25,26] and self doping.…”
Section: Introductionmentioning
confidence: 99%
“…The spinel ferrites of AB 2 O 4 have great application in the supercapacitors [1,2], photocatalysis [3,4], sensors [5,6], biomedical applications [7,8]. The most common combination is A site metal ions are Cu 2+ , Zn 2+ , Ni 2+ and B site are Fe 3+ , Al 3+ , respectively [9].…”
Section: Introductionmentioning
confidence: 99%